Identification and Characterization of a DmoB Flavin Oxidoreductase from a Putative Two-Component DMS C-Monooxygenase - Hammers, D. Scott (ACS Omega, 2020)
[Image: see text] The compound dimethyl sulfide (DMS) links terrestrial and oceanic sulfur with the atmosphere because of its volatility. Atmospheric DMS is responsible for cloud formation and radiation backscattering and has been implicated in climate control mitigation. The enzyme DMS C-monooxygenase degrades DMS and has been classified as a two-component FMNH(2)-dependent monooxygenase. This enzyme requires a flavin reductase B subunit to supply electrons to the monooxygenase A subunit where DMS conversion occurs. One form of the enzyme from Hyphomicrobium sulfonivorans has been isolated and characterized. In this work, a putative DMS C-monooxygenase has been identified with bioinformatics in Arthrobacter globiformis. We report the expression, purification, and characterization of the DmoB flavin reductase subunit, termed DmoB, from A. globiformis. Data support DmoB preference and optimal activity for the cosubstrates flavin mononucleotide (FMN) and NADH. FMN binds at a 1:1 stoichiometry with high affinity (K(d) = 1.11 μM). The reductase is able to generate product with the A subunit from H. sulfonivorans expressed in Escherichia coli, albeit at a lower turnover than the natively expressed enzyme. No static protein–protein interactions were observed under the conditions tested between the two subunits. These results provide new details in the classification of enzymes involved in the sulfur cycling pathway and emerging forms of the enzyme DMS monooxygenase.